1998
DOI: 10.1086/305778
|View full text |Cite
|
Sign up to set email alerts
|

Double Core Evolution. X. Through the Envelope Ejection Phase

Abstract: The evolution of binary systems consisting of an asymptotic giant branch star of mass equal to 3M ⊙ or 5M ⊙ , and a main sequence star of mass equal to 0.4M ⊙ or 0.6M ⊙ with orbital periods ∼ > 200 days has been followed from the onset through the late stages of the common envelope phase. Using a nested grid technique, the three-dimensional hydrodynamical simulations of an asymptotic giant branch star with radii ∼ 1 A.U. indicate that a significant fraction of the envelope gas is unbound (∼ 31% and 23% for bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
282
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(299 citation statements)
references
References 51 publications
15
282
2
Order By: Relevance
“…In both simulations this initial configuration results in the giant stars massively overflowing their Roche lobe radii. This is the case with many CE simulations (e.g., Sandquist et al 1998;Passy et al 2012a) and may have some effect on the CE outcome (Iaconi et al, 2016, in preparation). However, in the case of planetary companions, it is likely that the effect of starting close to the surface is minimal: companions as far as 2-3 stellar radii are likely to be captured (Villaver & Livio 2009;Mustill & Villaver 2012), but the angular momentum of the orbit transferred to the primary would confer to it only a relatively minor surface velocity of 1.1 − 1.3 km s −1 for the AGB star and 3.2 − 3.9 km s −1 for the RGB star (this range was found assuming that all the orbital angular momentum of the planet at a distance of 2-3 stellar radii is transferred to the envelope of the giant, and that this envelope rotates rigidly), not too different from our non-rotating initial models.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In both simulations this initial configuration results in the giant stars massively overflowing their Roche lobe radii. This is the case with many CE simulations (e.g., Sandquist et al 1998;Passy et al 2012a) and may have some effect on the CE outcome (Iaconi et al, 2016, in preparation). However, in the case of planetary companions, it is likely that the effect of starting close to the surface is minimal: companions as far as 2-3 stellar radii are likely to be captured (Villaver & Livio 2009;Mustill & Villaver 2012), but the angular momentum of the orbit transferred to the primary would confer to it only a relatively minor surface velocity of 1.1 − 1.3 km s −1 for the AGB star and 3.2 − 3.9 km s −1 for the RGB star (this range was found assuming that all the orbital angular momentum of the planet at a distance of 2-3 stellar radii is transferred to the envelope of the giant, and that this envelope rotates rigidly), not too different from our non-rotating initial models.…”
Section: Methodsmentioning
confidence: 95%
“…CE simulations using a variety of techniques (e.g. Sandquist et al 1998;Ricker & Taam 2012;Passy et al 2012a;Nandez et al 2014;Staff et al 2016) have a range of uncertainties and shortcomings (e.g., , but can be used as starting points to determine the nature of star-planet interactions. By running hydrodynamic simulations of the CE interaction between a 10 MJ planet and an RGB or an AGB star, we start addressing numerically aspects of the interaction such as the timescale of the interaction, the final separation or the extent to which the stellar envelope is spun-up.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) hydrodynamical studies of the CE phase have also been carried out (e.g., Terman, Taam, & Hernquist 1994;Rasio & Livio 1996;Livio & Soker 1988). Sandquist et al (1998) studied the stages when the envelope is ejected. Also, Bobrick et al (2017), found that jet appearance and quenching during CE can produce transient objects.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Livio & Soker (1988) and Rasio & Livio (1996) suggest that the energy is deposited in a very short time, because most of the gravitational energy is released at small orbital separations where the radius decreases quickly. On the other hand, Sandquist et al (1998) estimate that the overall timescale of the process lasts ∼200 days, while De Marco et al (2003) derived timescales of 9−18 yrs until a negligible amount of material remained in the envelope. The numerical simulations by Passy et al (2012), on the other hand, indicate a typical timescale of 100−200 days.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of rotation during the common envelope phase have been explored by Sandquist et al (1998), who showed that a differentially rotating structure, similar to a thick disk, surrounds the binary during an intermediate phase of the CE evolution. A similar thick disk structure was analytically obtained by Soker (1992Soker ( , 2004 and De Marco et al (2011).…”
Section: Introductionmentioning
confidence: 99%